1977
DOI: 10.1203/00006450-197705000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Trace Elements (Zinc, Cobalt, Selenium, Rubidium, Bromine, Gold) in Human Placenta and Newborn Liver at Birth

Abstract: Concentrations of zinc, cobalt, selenium, rubidium, bromium, and gold have been determined by neutron activation analysis in 18 placental and 6 liver tissue samples at birth. Their respective mean concentrations +/- standard deviations (parts per million) were 58 +/- 10, 0.060 +/- 0.036, 1.90 +/- 0.41, 14.0 +/- 3.5, 26.9 +/- 14.3, and 0.31 +/- 0.14 in placenta, and 651 +/- 257, 0.156 +/- 0.077, 4.52 +/- 1.96, 9.2 +/- 3.7,11.2 +/- 4.1, and 0.12 +/- 0.06 in liver tissue. Thus, we observed that the mean concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

1979
1979
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 0 publications
2
9
1
Order By: Relevance
“…The con tents within the fetal livers found by Widdow son et al (24) are larger only between the 20th and 30th weeks of gestation and agree there after. In the last period of pregnancy the Zn content of fetal livers agree quite well with those reported by Alexiou et al (1) (table IV), who has shown that the Zn content of the fetal liver also exceeds by far the Zn content of the maternal placenta.…”
Section: Zincsupporting
confidence: 81%
See 2 more Smart Citations
“…The con tents within the fetal livers found by Widdow son et al (24) are larger only between the 20th and 30th weeks of gestation and agree there after. In the last period of pregnancy the Zn content of fetal livers agree quite well with those reported by Alexiou et al (1) (table IV), who has shown that the Zn content of the fetal liver also exceeds by far the Zn content of the maternal placenta.…”
Section: Zincsupporting
confidence: 81%
“…The reduction of Rb (R = 0.7) in the fetal livers in comparison to the adult control group is in accordance with the finding of Alexiou et al (1) that the Rb content of fetal livers is reduced with respect to the maternal placenta (R = 0.8) indicating a diaplacental threshold for Rb. A similar reduc tion of Rb (R = 0.66) was observed in the fetal liver of rats (11) (table IV).…”
Section: Rubidiumsupporting
confidence: 79%
See 1 more Smart Citation
“…On the other hand, the lack of communication in the IWRM group may mean that the element is not causally related to the condition and further research is needed on this issue. In studies Alexiou et al [35] studied trace elements (zinc, cobalt, selenium, rubidium, bromine, gold) in the human placenta and in the liver of the newborn at birth, the authors note that the average concentration of essential trace elements (zinc, cobalt and selenium) were significantly higher in the liver than in the placenta, while interchangeable trace elements (rubidium, bromine, gold) were found in significantly higher concentrations in the placenta than in liver tissue.…”
Section: Placenta As An Indicator Of Fetal Selenium Contentmentioning
confidence: 98%
“…In Croatia, Alexiou et al, [35], indicated that Se in the placenta predicts birth of a child of normal weight, not intrauterine growth restriction. In this work, a significant positive relationship between placental Se and neonatal weight in a subgroup of pregnant women with body weight appropriate for this gestational age was established.…”
Section: Placenta As An Indicator Of Fetal Selenium Contentmentioning
confidence: 99%